THE MIDDLE PLEISTOCENE LARGE FELIDS (MAMMALIA) FROM BRECCE DI SOAVE (VERONA, N-E ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The fossils of large felids collected, in the so called "Brecce di Soave", by Angelo Pasa during the first half of XX century and stored at Museo di Storia Naturale di Verona are revised. Pasa referred these fossils to different taxa such as Panthera pardus, Panthera leo spelaea, Panthera sp. coming from different localities near Soave: Viatelle, Monte Zoppega, Sentiero, Castello, Monte Tenda. The term "Brecce di Soave" is used to define a karst filling deposits occurring on the Eocene limestones exposed near the village of Soave (Verona, NE Italy). The Brecce di Soave chronology is not homogeneous and includes different Pleistocene phases. The sites located in the Soave area can be referred at least to 2 different depositional phases: 1) around 1 Ma, as suggested by the occurrence of Mimomys, Allophaiomys, Beremendia, etc.; 2) around 0.5 Ma, characterized by the presence of Arvicola, Microtus (Terricola), Chionomys etc. Most of the fossils can be classified as Felidae indet. because of their fragmentary condition. All the other more complete remains can be referred to Panthera cf. P. fossilis with the exception of a partial M1 which has to be ascribed to Homotherium latidens (Viatelle) and a partial P4 referable to Canis cf. C. mosbachensis.
Keywords: Soave; North-Eastern Italy; Middle Pleistocene; Panthera fossilis